A bottom-up characterization of transfer functions for synthetic biology designs: lessons from enzymology - Carbonell-Ballesteros, Max; Durán-Nebreda, Salva; Montañez, Raúl; Macía, Javier; Rodríguez-Caso, Carlos Francisco (Oxfrod University Press, 2014)
Within the field of synthetic biology, a rational design of genetic parts should include a causal understanding of their input-output responses-the so-called transfer function-and how to tune them. However, a commonly adopted strategy is to fit data to Hill-shaped curves without considering the underlying molecular mechanisms. Here we provide a novel mathematical formalization that allows prediction of the global behavior of a synthetic device by considering the actual information from the involved biological parts. This is achieved by adopting an enzymology-like framework, where transfer functions are described in terms of their input affinity constant and maximal response. As a proof of concept, we characterize a set of Lux homoserine-lactone-inducible genetic devices with different levels of Lux receptor and signal molecule. Our model fits the experimental results and predicts the impact of the receptor's ribosome-binding site strength, as a tunable parameter that affects gene expression. The evolutionary implications are outlined.
Este artículo introduce un marco matemático innovador para diseñar dispositivos genéticos sintéticos, abordando las limitaciones de los enfoques tradicionales que ajustan datos experimentales a curvas de Hill sin considerar los mecanismos moleculares subyacentes. Mediante un enfoque inspirado en la enzimología, los autores describimos las funciones de transferencia en términos de constantes de afinidad al input y respuestas máximas. Este método permite predecir el comportamiento global de un dispositivo genético utilizando información detallada de sus partes biológicas. Como prueba de concepto, el estudio caracterizó dispositivos genéticos inducibles por lactonas de homoserina (Lux) con diferentes niveles del receptor Lux y moléculas señalizadoras. El modelo no solo se ajustó a los datos experimentales, sino que también predijo cómo la fuerza del sitio de unión al ribosoma del receptor puede modular la expresión génica, mostrando su utilidad como parámetro ajustable. Estos resultados ofrecen un marco teórico que mejora el diseño racional de circuitos genéticos y abren preguntas sobre sus implicaciones evolutivas.
Keywords: Enzimología; Synthetic Biology; Cellular computation; Cell engineering